The pth, qth and rth terms of an A.P. are a, b, c respectively. Show that (q – r) a + (r – p) b + (p -q) c = 0

Asked by Abhisek | 1 year ago |  62

#### 1 Answer

##### Solution :-

Let’s assume t and d to be the first term and the common difference of the A.P. respectively.

Then the nth term of the A.P. is given by, a= t + (n – 1) d

Thus,

ap = t + (p – 1) d = a  … (1)

aq = t + (q – 1) d = b  … (2)

ar = t + (r – 1) d = c  … (3)

On subtracting equation (2) from (1), we get

(p – 1 – q + 1) d = a – b

(p – q) d = a – b

$$d=\dfrac{a-b}{p-q}$$...........(4)

On subtracting equation (3) from (2), we get

(q – 1 – r + 1) d = b – c

(q – r) d = b – c

$$d=\dfrac{b-c}{q-r}$$.............(5)

Equating both the values of d obtained in (4) and (5), we get

$$\dfrac{a-b}{p-q}=\dfrac{b-c}{q-r}$$

$$(a - b)(q - r) = (b - c)(p - q)$$

$$aq - bq - ar+br =bp-bq-cp+cq$$

$$bp-cp+cq-aq+ar-br=0$$

By rearranging terms we get

$$(-aq+ar)+(bp-br)+(-cp+cq)=0$$

$$-a(q-r)-b(r-p)-c(p-q)=0$$

$$-a(q-r)+b(r-p)+c(p-q)=0$$

Therefore,$$(q-r)a+(r-p)b+(p-q)c=0$$ is proved.

Answered by Pragya Singh | 1 year ago

### Related Questions

#### Construct a quadratic in x such that A.M. of its roots is A and G.M. is G.

Construct a quadratic in x such that A.M. of its roots is A and G.M. is G.

Class 11 Maths Sequences and Series View Answer

#### Find the two numbers whose A.M. is 25 and GM is 20.

Find the two numbers whose A.M. is 25 and GM is 20.

Class 11 Maths Sequences and Series View Answer

#### If a is the G.M. of 2 and 1/4 find a.

If a is the G.M. of 2 and $$\dfrac{1}{4}$$ find a.

Class 11 Maths Sequences and Series View Answer

#### Find the geometric means of the following pairs of numbers

Find the geometric means of the following pairs of numbers:

(i) 2 and 8

(ii) a3b and ab3

(iii) –8 and –2

Class 11 Maths Sequences and Series View Answer

#### Insert 5 geometric means between 32/9 and 81/2.

Insert 5 geometric means between $$\dfrac{32}{9}$$ and $$\dfrac{81}{2}$$.

Class 11 Maths Sequences and Series View Answer